The princess test - Levine, Gail Carson (HarperCollinsPublishers, 1999)
In this humorous retelling of Hans Christian Andersen's "The Princess and the Pea," Lorelei must pass many difficult tests in order to prove that she is a true princess and win the hand of Prince Nicholas.